Transformation of a Sacred Landscape: Veneration of Amun-Re in Graffiti in the Valley of the Kings - Ragab, Muhammad R. (The journal of Egyptian archaeology, 2021)
More than 4000 graffiti are scattered throughout the Theban necropolis. Among them, around 2500 graffiti can be dated to Nineteenth, Twentieth, and Twenty-First Dynasties. These New Kingdom graffiti were made by members of the community of workmen from Deir el-Medina. Only a small group of no more than 120 graffiti consist of depictions of deities and veneration scenes. The interpretation of graffiti with depictions of Amun-Re on rock surfaces in the Valley of the Kings reveals valuable information regarding their locations. This study thus attempts to identify particular locations in the valley where the workmen of Deir el-Medina venerated Amun-Re in different forms. These spots may have been considered to be of religious significance to the workmen of Deir el-Medina.